SIOP Ependymoma I: Final results, long-term follow-up, and molecular analysis of the trial cohort—A BIOMECA Consortium Study. Issue 6 (9th January 2022) - Ritzmann, Timothy A; Chapman, Rebecca J; Kilday, John-Paul; Thorp, Nicola; Modena, Piergiorgio; Dineen, Robert A; Macarthur, Donald; Mallucci, Conor; Jaspan, Timothy; Pajtler, Kristian W; Giagnacovo, Marzia; Jacques, Thomas S; et al.
Abstract: Background: SIOP Ependymoma I was a non-randomised trial assessing event free and overall survival (EFS/OS) of non-metastatic intracranial ependymoma in children aged 3–21 years treated with a staged management strategy. A further aim was to assess the response rate (RR) of subtotally resected (STR) ependymoma to vincristine, etoposide, and cyclophosphamide (VEC). We report final results with 12-year follow-up and post hoc analyses of recently described biomarkers. Methods: Seventy-four participants were eligible. Children with gross total resection (GTR) received radiotherapy, whilst those with STR received VEC before radiotherapy. DNA methylation, 1q, hTERT, ReLA, Tenascin-C, H3K27me3, and pAKT status were evaluated. Results: Five- and ten-year EFS was 49.5% and 46.7%, OS was 69.3% and 60.5%. GTR was achieved in 33/74 (44.6%) and associated with improved EFS ( P = .003, HR = 2.6, 95% confidence interval (CI) 1.4–5.1). Grade 3 tumours were associated with worse OS ( P = .005, HR = 2.8, 95%CI 1.3–5.8). 1q gain and hTERT expression were associated with poorer EFS ( P = .003, HR = 2.70, 95%CI 1.49–6.10 and P = .014, HR = 5.8, 95%CI 1.2–28) and H3K27me3 loss with worse OS ( P = .003, HR = 4.6, 95%CI 1.5–13.2). Methylation profiles showed expected patterns. 12 participants with STR did not receive chemotherapy; a protocol violation. However, best chemotherapy RR was 65.5% (19/29, 95%CI 45.7–82.1), exceeding the prespecified 45%. Conclusions: Participants with totally resected ependymoma had the best outcomes. RR of STR to VEC exceeded the pre-specified efficacy criterion. However, cases of inaccurate stratification highlighted the need for rapid central review. 1q gain, H3K27me3 loss, and hTERT expression were all associated with poorer survival outcomes.